Validation of the prolapse quality of life questionnaire PQOL: an Afrikaans version in a South African population - Corlia Brandt; Cornel Van Rooyen; Hennie Cronje (South African Medical Association, 2016)
Introduction: The Prolapse Quality of Life questionnaire (P-QoL) has been validated and translated into eight languages. The lack of an Afrikaans version of the P-QoL limits studies in Afrikaans speaking patients with Pelvic Organ Prolapse (POP). The aim was to validate an Afrikaans version of the P-QoL in a South African population.Methodology: The P-QoL questionnaire was translated to Afrikaans by a medical translator and three gynaecologists. This descriptive study determined construct validity comparing 25 symptomatic (64.1% n=39) and 14 asymptomatic (35.9% n=39) participants` median domain scores. The POP stage was determined according to the Pelvic Organ Prolapse Quantification (POP-Q) scale and compared to their domain scores by means of percentages. A second P-QoL questionnaire was completed and the stability determined by the test-retest method. The cronbach alpha was used to determine internal consistency and the kappa value to determine measure of agreement.Results: Symptomatic participants had higher median domain scores than asymptomatic participants. All asymptomatic participants had stage O POP and 33.3% of symptomatic participants had stage III POP. Stability was good with an average of above 50%. The mean Cronbach alpha value was 0.94 and the kappa value indicated moderate to good strength of agreement between items (к = 0.41-0.80).Conclusion: The Afrikaans P-QoL questionnaire was found valid and reliable to determine quality of life in women with POP, correlating with the findings of other validation studies and supporting the evidence that the P-QoL is a high-quality disease-specific quality of life questionnaire.Word count: 244Keywords:, Pelvic Organ Prolapse, Quality of Life (questionnaire), Uterovaginal prolapse, Validation